2016
DOI: 10.1016/j.isjp.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The TeaM ( T h e r a peutic M ammaplasty) study: Protocol for a prospective multi-centre cohort study to evaluate the practice and outcomes of therapeutic mammaplasty

Abstract: HighlightsMulticentre prospective study involving breast and plastic surgical units across the UK.Will produce valuable data regarding the practice and outcomes of therapeutic mammaplasty.Will inform decision-making and lead to future definitive study.Will strengthen the collaborative network to facilitate the delivery of future projects.Will increase awareness of the techniques among trainees such that participation is educational.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The methods for the iBRA‐2 and TeaM prospective cohort studies have been reported previously. The two studies collected identical data items during an overlapping time interval and 37 centres participated in both studies, supporting the validity of a pooled analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods for the iBRA‐2 and TeaM prospective cohort studies have been reported previously. The two studies collected identical data items during an overlapping time interval and 37 centres participated in both studies, supporting the validity of a pooled analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Consecutive patients undergoing mastectomy with or without IBR for invasive or preinvasive breast cancer at participating centres between July and December 2016 were recruited prospectively to the iBRA‐2 study. Patients undergoing TM, defined as ‘the oncoplastic application of breast reduction or mastopexy techniques including removal of skin to reduce the skin envelope to treat invasive or pre‐invasive (ductal carcinoma in situ ; DCIS) breast cancer using breast conserving surgery’, at participating centres between 1 September 2016 and 30 June 2017 were recruited to the TeaM study. The surgeon‐reported indication for offering TM was recorded prospectively, and only the subgroup of patients offered TM to avoid mastectomy were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, to date, there is consistent but low‐level evidence of better QoL outcomes and non‐inferior oncological outcomes with OBCS techniques. The planned UK prospective multicentre Therapeutic Mammoplasty (TeaM) study will provide high‐quality evidence regarding both aspects for that group of procedures . In the meantime, we feel that the broader application of OBCS techniques can continue to safely evolve as long as the principles of good surgical cancer management are followed.…”
mentioning
confidence: 99%